The Impact of the Covid-19 on the Word of Education - Do’ana Adinda Nalurita; Arief Syamsuddin Muhammad Olii (Green Publisher Indonesia, 2021)
This article examines the impact of Covid-19 on the word of education. Which has the aim of knowing how nfluential Covid-19 on education. It is because education is a conscious effort that is carried out systematically in creating an atmosphere of teaching and learning so that students can develop their potentials in live. So that later it will be an educated person is very important. Being an educated person is very important as it will make someone eligible for the nation. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. The results of the studyAlthough many educataors, students and the community are not ready yet facing the era of the industrial revolution 4.0, courageous learning in the midst of this Covid-19 pandemic as if forcing all humans to be ready for today’s technological developments. From a sociological perspective, this policy is the right step to take under these conditions.